2023
DOI: 10.1177/01461672231202756
|View full text |Cite
|
Sign up to set email alerts
|

Why Do People Think Individuals in Poverty Are Less Vulnerable to Harm?: Testing the Role of Intuitions About Adaptation

Nathan N. Cheek,
Jackson Murray

Abstract: People often falsely believe that individuals from low socioeconomic status (SES) backgrounds are less harmed than those from higher SES backgrounds by a wide range of negative events. We report three studies (total N = 1,625) that provide evidence that this “thick skin bias” emerges at least in part because people overgeneralize otherwise accurate intuitions about adaptation. Across studies, participants accurately intuited that people adapt to psychophysical experiences (e.g., brightness, weight, and volume)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…Previous research documented biases in perceived physical pain potentially attributable to the perception that Black individuals have experienced more hardship than White individuals, and the assumption that hardship reduces vulnerability to physical pain (Hoffman & Trawalter, 2016). We extended this logic to propose that low-SES individuals are perceived as having been "toughened" by their hardship (see also Cheek & Murray, 2023), causing them to be less affected by new negative events. Across dozens of studies, we have found that lay people, Consumer Vulnerability in Poverty 10 including a nationally representatively sample of U.S. citizens, and professionals such as therapists and teachers believe that lower-SES individuals are less impacted both by trivial and by more consequential negative events.…”
Section: The "Thick Skin Bias" As a Source Of Vulnerabilitymentioning
confidence: 95%
“…Previous research documented biases in perceived physical pain potentially attributable to the perception that Black individuals have experienced more hardship than White individuals, and the assumption that hardship reduces vulnerability to physical pain (Hoffman & Trawalter, 2016). We extended this logic to propose that low-SES individuals are perceived as having been "toughened" by their hardship (see also Cheek & Murray, 2023), causing them to be less affected by new negative events. Across dozens of studies, we have found that lay people, Consumer Vulnerability in Poverty 10 including a nationally representatively sample of U.S. citizens, and professionals such as therapists and teachers believe that lower-SES individuals are less impacted both by trivial and by more consequential negative events.…”
Section: The "Thick Skin Bias" As a Source Of Vulnerabilitymentioning
confidence: 95%